Constitutional dismemberment via referenda: a comparative overview - Scotti, Valentina Rita (Revista de Investigações Constitucionais, 2020)
Constitutional dismemberment is one of the main consequences attached to constitutional amendments that Albert's book analyses. After having analyzed Albert’s definition, the present essay focuses on the practice of constitutional dismemberment via referendum and discusses whether, in times of populism and democratic decay, the constitutional design should provide for specific measures in order to protect the political opposition from the allegiance between the populist leadership and the majority of the population. Building on the existing literature and on a comparative analysis, the essay concludes by highlighting the pros and cons of introducing special protections for political minorities during constitutional referenda to protect democracy against populist deviations, suggesting the need to provide further studies in this field.